Novel approaches of nanotechnology in food - Grumezescu, Alexandru Mihai (Nanotechnology in the agri-food industry ;, 2016)
This book offers an overview of the potential applications of nanotechnology in food science and industry, discussing potential advancements of nanotechnology in the food industry and providing a reference for how novel approaches to nanotechnology can advance food science through proven research results and industrial applications.